PERKEMBANGAN REGULASI RUMAH IBADAT DALAM KONTEKS NEGARA BANGSA (NKRI) PERSPEKTIF MAQASHID AL-SYARI’AH - Sukandi Sukandi (LP2M Universitas Ibrahimy, 2020)
The background of this research is the phenomenon that occurs in the Indonesian society that shows the gap between das sein and das sollen. Evidenced by the destruction, rejection, and burning of houses of worship. Rules should bring benefit to all people, not only to the majority. The rejection of the majority community towards the establishment of the Synagogue is a sign that there is a possibility of errors in the regulations or the community. The method used is the library method. The results of this study are the development of the houses of worship regulations can be grouped into two models. The first model is to detail or complete the previous regulations, which are in the licensing, monitoring and conflict resolution items. The second model is to bring up new regulations that did not exist in the previous regulations, namely in the presence of the religious harmony forum (FKUB) items and sources of funds, temporary houses of worship, temporary permits for building utilization, and transition mechanisms. While the second formulation produced Maqashid Al-Shari'ah's views on the development of the houses of worship regulations can be categorized into three groups. The first category is Dharuriyat, namely: the establishment of houses of worship and the formation of the religious harmony forum (FKUB). The second category is Hajiyat, the main purpose of making regulations on houses of worship is the realization of religious harmony under the auspices of the religious harmony forum (FKUB). They are: Supervision, Reporting and Resolution of conflicts. The third category is Tahsiniyat, if this regulation is not enforced it will not interfere with the realization of the main objective. This regulation is in the form of: Temporary Worship House, Temporary Permit for Building Utilization and Transition Mechanism for Worship.